Pembelajaran aktif dalam kursus kerja sosial dan perundangan melalui kempen kesedaran berkaitan perundangan sosial - Nur Saadah Mohamad Aun; Nor Jana Saim; Norulhuda Sarnon@Kusenin (Penerbit Universiti Kebangsaan Malaysia, 2021)
There is interrelationship between the professions of social work and the legal system. A social worker, in the role of advocate ensures the clients’ rights in general as well as to provide social justice such as social legislation awareness campaign. In order to that, this paper aimed to enlighten the implementation of a social legislation awareness campaign, which is one of the active learning methods with reference to social marketing theory. The implementation of the awareness campaign involves active teaching and learning activities for the course Social Work and Social Legislation (SKPW5102); a postgraduate course for Postgraduate Diploma of Social Work. The campaign aimed to raise awareness of the public about social legislation. Furthermore, the campaign is very much in a collaboration of the administration of Terminal Bersepadu Selatan and Institut Sosial Malaysia. The implementation of this campaign is a sequence of reflective teaching from the similar courses. Prior to that, the students were exposed to the court trials for hearing cases relatedto social issues such as crimes among juveniles and were asked to write reflections from their experiences. The learning method won bronze medal during the K-Novasi 2015. However, after several years of implementing the method, a new approach with the implementation of the campaign was implemented for the assessment of Social Work and Social Justice course.